Pendekatan Parsipatory Santri Musthafawiyah Purbabaru Dalam Melihat Hukum Menjual Harta Wakaf Menurut Ulama Pondok Pesantren (Perspektif Pengabdian Kepada Mayarakat ) - Ahmad Zuhri; Khairil Iman (Jurnal Abdi Mas Adzkia, 2022)
AbstractThere is a tradition of Mustafawiyah students known as Pondok Waqf (Pondok Waqf). This waqf is carried out by students who have finished studying with juniors with the aim of helping juniors who do not have a cottage and to get rewards only, and of course the implementation is only verbal and without administration. This research is an empirical juridical research using a participatory approach. The research data was collected by means of interviews and document studies and then analyzed using the Miles and Huberman method. The results of this study indicate that the practice of Waqf Boarding among Pon-Pes Mustafawiyah Purbabaru students is carried out with the habit of students waqf their cottage to their juniors on the basis of trust and hoping for a reward, Wakap Pondok is done orally. , without witnesses, without Nazir and without proper administration. . There are several factors behind the sale of waqf huts among Purbabaru Mustafawiyah Santri, namely the lack of assistance and attention from teachers and boarding school administrators for waqf students in banjar, lack of knowledge and access to information related to waqf management regulations and low legal awareness. musthafawiyah students in wakap. . The cleric of the Mustafawiyah Purbabaru Islamic Boarding School is of the opinion that waqf assets should not be traded based on the opinion of Umar bin Khattab narrated by Imam Bukhari. Thus, the law of selling waqf huts is haram and the perpetrator is a sinner